Identifying Problems in Students’ Final Projects Based on Scientific Writing Guidelines - Ernawati, Endang (Bina Nusantara University, 2010)
Article analyzed student’s difficulties and abilities in writing their final projects, which were undergraduate theses and undergraduate paper conducted by some students at the English Department, Bina Nusantara University. This was a preliminary study to support an appropriate student guideline in writing their final project. The study was conducted by applying qualitative methods that was by analyzing the four theses and one paper in terms of their format: titles, introduction, theoretical background, analysis, conclusion, bibliography, and paper rubric to analyze the contents. It can be concluded that generally, students, guided by their mentor/lecturer, understand the final paper guidelines and they are able to apply it in their thesis and paper. But, there are still lack of clarity and relevancy in expressing their ideas properly, and their ability in writing in both English and Bahasa Indonesia must be improved. These problems can be overcome by socializing the writing guidelines to both students and lecturers, providing them with critical thinking skills, cooperation with library that will guide them in information literacy skills, and language center that will improve their writing skills.